Multichannel harmonic and percussive component separation by joint modeling of spatial and spectral continuity - Duong, Ngoc Q. K.; Tachibana, Hideyuki; Vincent, Emmanuel; Ono, Nobutaka; Gribonval, Remi; Sagayama, Shigeki (2011 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP), 2011)
This paper considers the blind separation of the harmonic and percussive components of multichannel music signals. We model the contribution of each source to all mixture channels in the time-frequency domain via a spatial covariance matrix, which encodes its spatial characteristics, and a scalar spectral variance, which represents its spectral structure. We then exploit the spatial continuity and the different spectral continuity structures of harmonic and percussive components as prior information to derive maximum a posteriori (MAP) estimates of the parameters using the expectation-maximization (EM) algorithm. Experimental results over professional musical mixtures show the effectiveness of the proposed approach.